Complement, Not Substitute: An Integrative Review of Teacher’s Pedagogical Roles in AI-Mediated Learning Environments - Parajuli, Kewal Ram; Pokhrel, Shantanu (Rupantaran: A Multidisciplinary Journal, 2026)
Artificial intelligence (AI) is shifting from peripheral tools to core learning infrastructure. With the increasing use of artificial intelligence (AI) technology in educational settings, there is a growing need to explore how teachers can enhance their pedagogical roles and skills in AI-mediated learning environments. This study provides insights into in what way teachers can adapt and innovate their pedagogical roles to effectively prepare students for the digital age. This study employed a qualitative research approach through an integrative review research design, literature from 2016-2025, issues related to human and AI co-design and classroom orchestration. It is found that AI supported formative assessment and feedback, teacher AI/data literacy with ethical governance, and simulation based professional learning through conceptual, empirical, and policy publications on the changing pedagogical functions of teachers in AI-mediated learning settings. Artificial intelligence makes the most significant contributions to education when it supports, rather than replacing, the fundamental human effort of teaching. When analytics are used as indicators, feedback tools are used as instruments of learning, and simulations are used as a space to safely practice, artificial intelligence becomes a complement to human judgment, rather than a substitute.